HUBUNGAN INTENSITAS PENGGUNAAN MEDIA SOSIAL DAN STRES DENGAN KUALITAS TIDUR PADA MAHASISWA KESEHATAN MASYARAKAT UPN VETERAN JAKARTA TAHUN 2022 - Bunga Anggita, (2022)
Sleep is a basic human need, humans have different sleep needs. Inadequate sleep can cause poor sleep quality. Factors that can affect sleep quality include the use of social media and stress. This study aims to determine the relationship between the intensity of social media use and stress with sleep quality in public health students at UPN Veteran Jakarta in 2022 by using quantitative methods, cross-sectional approaches, and the proportional stratified random sampling technique. Based on the analysis of the Spearman test, it was found that there was a positive correlation with a moderate relationship between the intensity of social media use (p-value 0.000 and r 0,256) and stress (p-value 0.000 and r 0,260) with sleep quality. However, there was no correlation between age (p-value 0.075 and r -0,120) and gender (p-value 0.306 and r -0,069) with sleep quality. Therefore, students need to pay attention to the body's need for sleep by limiting the use of social media and coping with stress. Keywords: Sleep Quality, Students, Social Media, Stress